Case Report: Noninvasive Clinical Intervention of REBACIN® on Histologic Regression of High Grade Cervical Intraepithelial Neoplasia - Wang, Fan; Liu, Rong; Ma, Yan; Wu, Dai-Fei; Deng, Liu-Hong; Wang, Sheng; Wang, Gui-Yu; Zhang, Chun-Fa; Qu, Quan-Xin (Frontiers in Medicine, 2021)
High-risk human papillomavirus (hrHPV) persistent infection is the major cause of cervical cancer. Clinical intervention of hrHPV-associated high-grade squamous intraepithelial lesion (HSIL) is critical to prevent cervical cancer, and current treatment is surgery (an invasive therapy). However, some patients refuse to do so for an afraid of potential adverse effects on future fertility or other concerns which creates a critical need for development of non-invasive therapeutic strategies. Here, we report for the first time the cases of non-invasive intervention with REBACIN®, a proprietary antiviral biologics, in clinical treatment of HSIL. From 12,958 visiting patients assessed for eligibility, 18 HSIL-patients with cervical intraepithelial neoplasia-grade 2, positive of both diffused overexpression of p16 and high-risk HPV were enrolled in this non-invasive clinical intervention mainly due to concerns of future fertility. REBACIN® was administered intravaginally every other day for three months (one-course) except during menstrual period, and were followed up for 6-36 months for the examination of high-risk HPV DNA, cervical cytology and histopathology. After one to three course treatments, most cases (16/18) displayed both the regression from HSIL (CIN2) to normal cervical cytology and clearance of high-risk HPV infection. Further studies demonstrated REBACIN® significantly suppressed HPV16 E7 oncoprotein expression in a human cervical cancer cell line, which is consistent with previous finding that REBACIN® inhibits the growth of tumors induced by expression of E6/E7 oncogenes of either HPV16 or HPV18. This report indicates REBACIN® as a novel effective non-invasive clinical intervention for HSIL-patients as well for high-risk HPV persistent infection, providing a new clinical option for the non-invasive treatment of hrHPV-associated high-grade squamous intraepithelial lesion, which is worthy of further research on clinical validation and application.